Waking Up in Pain: a prospective unselected cohort study of pain in 3702 patients immediately after surgery in the Danish Realm. Issue 11 (18th August 2021) - Rasmussen, Anders Mølgaard; Toft, Mette Helene; Awada, Hussein Nasser; Dirks, Jesper; Brandsborg, Birgitte; Rasmussen, Line Kirkegaard; Kirkegaard, Ellen; Hasfeldt-Hansen, Dorthe; Larsen, Thomas Egemose; Charalampidis, Georgios; Mørk, Emilie Louise Schjøtt; Rosager, Chirstine Linaa; et al.
Abstract : Background: Acute and persistent pain after surgery is well described. However, no large-scale studies on immediate postoperative pain in the operating room (OR) exist, hindering potential areas of research to improve clinical outcomes. Thus, we aimed to describe the occurrence and severity of immediate postoperative pain in a large, unselected cohort. Methods: This was a prospective cohort study, encompassing all procedures in 31 public hospitals in the Danish Realm, during a 5-day period including the weekend. Data on procedures and anesthesia were collected and the main outcome was occurrence of moderate or severe pain in the OR. Secondary outcomes included pain, sedation and nausea in the OR or during the first 15 min in the postanesthesia care unit (PACU) including relevant risk factors. Descriptive and logistic regression statistics were used. Results: A total of 3675 procedures were included for analysis (87% inclusion rate). Moderate or severe pain occurred in 7.4% (95% CI 6.5% to 8.3%) of cases in the OR immediately after awakening, rising to 20.2% in the OR and/or PACU. Large intraprocedure and interprocedure variations occurred (0.0%–37.5%), and in 20% of cases with epidural-general anesthesia patients experienced moderate or severe pain. Independent risk factors were female sex, younger age, preoperative pain, daily opioid use and major surgical procedures. Conclusion: Moderate or severe pain in the immediate postoperative phase occurred in 20% of all cases with procedure and anesthesiological technique variations, suggesting a need for identification of relevant procedure-specific risk factors and development of preventive treatments. Trial registration number: RoPR ID 43191.